Analysing endometrial microbiome: methodological considerations and recommendations for good practice. Issue 4 (3rd February 2021) - Molina, Nerea M; Sola-Leyva, Alberto; Haahr, Thor; Aghajanova, Lusine; Laudanski, Piotr; Castilla, Jose Antonio; Altmäe, Signe
ABSTRACT: There is growing evidence that the upper female genital tract is not sterile, harbouring its own microbial communities. However, the significance and the potential effect of endometrial microorganisms on reproductive functions remain to be fully elucidated. Analysing the endometrial microbiome, the microbes and their genetic material present in the endometrium, is an emerging area of study. The initial studies suggest it is associated with poor reproductive outcomes and with different gynaecological pathologies. Nevertheless, studying a low-biomass microbial niche as is endometrium, the challenge is to conduct well-designed and well-controlled experiments in order to avoid and adjust for the risk of contamination, especially from the lower genital tract. Herein, we aim to highlight methodological considerations and propose good practice recommendations for future endometrial microbiome studies.